Branched-chain amino acid supplementation attenuates muscle soreness, muscle damage and inflammation during an intensive training program - Matsumoto, K.; Koba, T.; Hamada, K.; Sakurai, M.; Higuchi, T.; Miyata, H. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM: The aim of this paper was to assess the effects of branched-chain amino acid (BCAA) supplementation on muscle soreness, muscle damage and inflammation during an intensive training program. METHODS: Twelve long-distance runners (20±1 year-old) participated in a double-blinded crossover designed study conducted during two intensive training periods (three-day). The subjects were provided either a drink containing BCAA (0.8% BCAA in a 3.5% carbohydrate solution; 2,500 mL/day) or an isocaloric placebo drink during each training period. All subjects completed the same training program (total running distance: males: 86 km, females: 64 km), and ate the same meals during the training period. Whole body muscle soreness and fatigue sensation were measured in the morning before and during the training period by Visual Analogue Scale method. Plasma creatine kinase (CK), lactate dehydrogenase (LDH), and granulocyte elastase (GEL) levels were measured as indicators of muscle damage and inflammation before and after the training period. RESULTS: Muscle soreness and fatigue sensation during the training period in the BCAA trial were lower than those in the placebo trial (-32% and -24%, respectively; P<0.05). The plasma CK, LDH, and GEL levels after the training program in the BCAA trial were lower than those in the placebo trial (-21%, -6%, and -15%, respectively; P<0.05). CONCLUSIONS: These results demonstrate that BCAA supplementation during an intensive training program effectively reduces the muscle soreness and fatigue sensation, and that the perceived changes could be attributed to the attenuation of muscle damage and inflammation.